Incubating Farmer Producer Companies: The Missing Middle - Richa Govil; Annapurna Neti
Thousands of farmer-producer companies (FPCs) have been registered in India due to national and state policies. Given their resource-constrained environments, most FPCs face myriad challenges and are struggling to become viable. While the policies provide for incubation support for FPCs, the level of support has been inconsistent and inadequate. This paper proposes a framework for classifying FPCs and their differing incubation needs and advocates for a stronger incubation ecosystem for FPCs, moving away from a one-size-fits-all approach. It also suggests prioritising incubation support for an oft-overlooked category of FPCs with the potential for generating remunerative returns.